2019
DOI: 10.1103/physrevb.100.014435
|View full text |Cite
|
Sign up to set email alerts
|

Interface moment dynamics and its contribution to spin-transfer torque switching process in magnetic tunnel junctions

Abstract: A practical problem for memory applications involving perpendicularly magnetized magnetic tunnel junctions is the reliability of switching characteristics at high-bias voltage. Often it has been observed that at high-bias, additional error processes are present that cause a decrease in switching probability upon further increase of bias voltage. We identify the main cause of such error-rise process through examination of switching statistics as a function of bias voltage and applied field, and the junction swi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Additional evidence for an origin associated with the heavymetal/ferromagnet interface comes from the fact that the large-∆ linewith is very sensitive to applied DC current (see supplemental information), consistent with a very thin and/or low-moment region under the influence of the spin current generated by the heavy metal. Our observations might be related to recent findings from the IBM group of interfacial regions in CoFeB/MgO/CoFeB magnetic tunnel junctions whose dynamics can become partially decoupled from the bulk of the magnetic films [21,22]. The two experiments differ, however, in that the IBM work deduced a difference in effective magnetic anisotropy (compared to the bulk of the magnetic film) for the interfacial layers at CoFeB/MgO interfaces, while in our devices the large-∆ resonance corresponds to an increased damping near a Pt/ferromagnet interface without a large difference in anisotropy.…”
Section: A Results Of Lineshape Analysessupporting
confidence: 82%
“…Additional evidence for an origin associated with the heavymetal/ferromagnet interface comes from the fact that the large-∆ linewith is very sensitive to applied DC current (see supplemental information), consistent with a very thin and/or low-moment region under the influence of the spin current generated by the heavy metal. Our observations might be related to recent findings from the IBM group of interfacial regions in CoFeB/MgO/CoFeB magnetic tunnel junctions whose dynamics can become partially decoupled from the bulk of the magnetic films [21,22]. The two experiments differ, however, in that the IBM work deduced a difference in effective magnetic anisotropy (compared to the bulk of the magnetic film) for the interfacial layers at CoFeB/MgO interfaces, while in our devices the large-∆ resonance corresponds to an increased damping near a Pt/ferromagnet interface without a large difference in anisotropy.…”
Section: A Results Of Lineshape Analysessupporting
confidence: 82%
“…With these accurate torques, high bias was predicted to lead to undesired switching of the fixed layer, which then induces fast perpetual cyclic switching of both the FL and pinned layers, as indeed compatible with some experimental observations [12]. This survey of the studies of back hopping indicates two proposed origins of the phenomenon: the bias dependence of the torques acting on the FL [4][5][6], or the dynamics of the reference layer [9][10][11][12]. In this work, we discriminate between these two scenarios by measuring in a single-shot time-resolved manner the BH in several MTJs having different FLs but sharing a fixed system with layers of identical nominal compositions.…”
Section: Introductionsupporting
confidence: 80%
“…We therefore turn to the second proposed scenario [2,[9][10][11], which suggested that some "subsystem" within the fixed layers system is destabilized by STT once the FL has switched. This subsystem affects the MTJ resistance and must thus include a switching of at least the SPL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations